Validated age, growth and maturity of the bonnethead Sphyrna tiburo in the western North Atlantic Ocean. Issue 3 (15th July 2014) - Frazier, B. S.; Driggers, W. B.; Adams, D. H.; Jones, C. M.; Loefer, J. K.
<x xml:space="preserve">Abstract</x> The age, growth and maturity of bonnetheads Sphyrna tiburo inhabiting the estuarine and coastal waters of the western North Atlantic Ocean (WNA) from Onslow Bay, North Carolina, south to West Palm Beach, Florida, were examined. Vertebrae were collected and aged from 329 females and 217 males ranging in size from 262 to 1043 mm and 245 to 825 mm fork length, LF, respectively. Sex‐specific von Bertalanffy growth curves were fitted to length‐at‐age data. Female von Bertalanffy parameters were L∞ = 1036 mm LF, k = 0·18, t0 = −1·64 and L0 = 272 mm LF. Males reached a smaller theoretical asymptotic length and had a higher growth coefficient (L∞ = 782 mm LF, k = 0·29, t0 = −1·43 and L0 = 266 mm LF). Maximum observed age was 17·9 years for females and 16·0 years for males. Annual deposition of growth increments was verified by marginal increment analysis and validated for age classes 2·5+ to 10·5+ years through recapture of 13 oxytetracycline‐injected specimens at liberty in the wild for 1–4 years. Length (LF50) and age (A50) at 50% maturity were 819 mm and 6·7 years for females, and 618 mm and 3·9 years for males. Both female and male S. tiburo in the WNA had a significantly higher maximum observed age, LF50, A50 and L∞, and a significantly lower k and estimated L0 than evident in the Gulf of Mexico (GOM). These significant differences in life‐history parameters, as well as evidence from tagging and genetic studies, suggest that S. tiburo in the WNA and GOM should be considered separate stocks.